Critical Factors in Road Infrastructure Investment Effectiveness : A Study in Dong Phu District, Binh Phuoc Province - Nguyen Phu Dai (International Journal of Scientific Research in Civil Engineering, 2024)
This study aims to evaluate the effectiveness of road infrastructure investment projects in Dong Phu District, Binh Phuoc Province, from 2020 to 2023. The research adopts a comprehensive methodological approach, incorporating descriptive statistical analysis, Cronbach’s Alpha, KMO, and Bartlett’s tests, and multiple linear regression models to identify key determinants of project success. Data were collected through surveys involving 105 employees in the transportation and construction sectors, complemented by secondary data from local reports. The findings reveal that investment capital mobilization and management are the most significant factors influencing project outcomes, with a standardized coefficient (Beta) of 0.449. Other critical determinants include the planning and development of the transportation sector (Beta = 0.433), the performance of the project owner and management board (Beta = 0.396), and quality management of road construction projects (Beta = 0.255). These results underscore the need for innovative financial mechanisms, strategic planning, and enhanced management practices to ensure the long-term effectiveness and sustainability of infrastructure investments. The study contributes valuable insights for policymakers and stakeholders, offering practical recommendations to improve the planning, execution, and management of road infrastructure projects in developing regions like Dong Phu District.